Active tectonics of the Alhama de Murcia fault, Betic Cordillera, Spain - Martínez-Díaz, J.J.; Masana, E.; Ortuño, M. (Journal of Iberian Geology, 2012)
We present an overview of the knowledge of the structure and the seismic behavior of the Alhama de Murcia Fault (AMF). We utilize a fault traces map created from a LIDAR DEM combined with the geodynamic setting, the analysis of the morphology, the distribution of seismicity, the geological information from E 1:50000 geological maps and the available paleoseismic data to describe the recent activity of the AMF. We discuss the importance of uncertainties regarding the structure and kinematics of the AMF applied to the interpretation and spatial correlation of the paleoseismic data. In particular, we discuss the nature of the faults dipping to the SE (antithetic to the main faults of the AMF) in several segments that have been studied in the previous paleoseismic works. A special chapter is dedicated to the analysis of the tectonic source of the Lorca 2011 earthquake that took place in between two large segments of the fault.